THE RELATIONS OF JAPAN WITH THE COUNTRIES OF CENTRAL ASIAN REGION - Садыкова Р. O. (International relations and international law Journal, 2016)
This article is devoted to the problem of economic relations of Japan with Central Asian countries. The author paid an attention to the establishment and development of economic relations between the countries of Central Asian and Japan, its main stages and directions.